Binaries need to shatter for bodies to matter: Do disembodied masculinities undermine organizational ethics?. (March 2015) - Knights, David
Arguing that binaries and their relationship to masculinities operate to constrain the development of corporeal or embodied ethics in organizations, this article seeks to advance their deconstruction and dissolution. If bodies are to matter, binaries need to shatter. First, it deconstructs the binary by examining the epistemological space between representations of life, language, labour and gender and the assumptions of subjectivity that are their conditions of possibility. Recognizing deconstruction to have some limitations in terms of subscribing to cognitive and perhaps masculine discourses, the article turns secondly to two literatures that seek to dissolve binary constructions ontologically. By combining epistemological deconstructions and ontological dissolutions, the second of these approaches facilitates the development of an embodied and embedded approach to organizational ethics that disavows dominant discourses of masculinity. The article then has two central objectives of first documenting the dominance of masculine, disembodied binary thinking in organizations and society and second, of examining ways through which it may be deconstructed and dissolved so as to enable an embodied ethics of engagement in organizations.